2004
DOI: 10.1097/00005082-200401000-00007
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Body Awareness in Persons With Heart Failure Treated Medically or With Transplantation

Abstract: Heart failure is a chronic disabling problem afflicting a growing number of adults. These individuals experience episodes of exacerbation demonstrated by increasing shortness of breath, fatigue, and fluid retention. The symptoms often develop in a slow and insidious manner making perception of worsening difficult to determine. Theoretically, an increase in body awareness may help individuals recognize symptoms of worsening heart failure earlier, but it is not known whether increased body awareness leads to som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 29 publications
4
47
1
Order By: Relevance
“…Much of the earlier literature considers a patient’s attentional focus on body symptoms as an expression of anxiety, depression, or somatization [1]. For example, the terms body awareness and somatic awareness have been used in studies of anxiety and panic disorders to describe a cognitive attitude characterized by an exaggerated focus on physical symptoms, magnification (“somatosensory amplification”), rumination, and catastrophic outcome beliefs [2].…”
Section: Introductionmentioning
confidence: 99%
“…Much of the earlier literature considers a patient’s attentional focus on body symptoms as an expression of anxiety, depression, or somatization [1]. For example, the terms body awareness and somatic awareness have been used in studies of anxiety and panic disorders to describe a cognitive attitude characterized by an exaggerated focus on physical symptoms, magnification (“somatosensory amplification”), rumination, and catastrophic outcome beliefs [2].…”
Section: Introductionmentioning
confidence: 99%
“…The emotions were described as either negatively toned or positively toned. Study has demonstrated that BA may be used to monitor physical cues associated with stress and provide a start for stress reduction interventions (Baas et al, 2004). The finding in our study of a shift from the body to the outside world was initiated by either the participants themselves or by a world presenting meaningful and enjoyable activities.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological factors, notably distress, depressive mood, and somatization, have been implicated in the transition to chronic low back pain (Pincus, Burton, Vogel, & Field, 2002). Investigations have also exposed the advantages regarding the ability to notice subtle body sensations and that it may be useful in the management of chronic diseases, such as congestive heart failure (Baas, Berry, Allen, Wizer, & Wagoner, 2004), chronic renal failure (Christensen, Wiebe, Edwards, Micheles, & Lawton, 1996), and chronic low back pain (Mehling, Hamel, Acree, Byl, & Hecht, 2005). Improved BA may change the attitude to one’s own body, enhance the ability to listen to bodily symptoms, and increase sense of control in daily life.…”
mentioning
confidence: 99%
“…Higher scores indicate a higher degree of body awareness. The value of Cronbach's alpha has been reported in previous studies to be between 0.80 and 0.88 [19,36]. The Swedish validated version of the BAQ scale was used.…”
Section: Instrumentmentioning
confidence: 99%